Evaluation of the relationship between emotional and behavioral problems and quality of life of adolescents in school. (13th December 2019) - Hendekçi, Ayla; Bilgin, Sonay
This study was conducted to determine the quality of life and difficulties of adolescents in school age. This descriptive study was conducted in a city center three secondary School. Similarly from each school 114, 114, 116 people participated in the study, 4 students could not be included in the study due to insufficient data and the study was completed with 344 students. Questionnaire developed by the researcher, the Strengths and Difficulties Questionnaire (SDQ), and the Pediatric Quality of Life Inventory (PedsQL) were used for data collection. Research was completed in line with the ethical principles. According to the evaluations, it was observed that 50.6% of the students was 13 years old, 52% was male, and 53.5% was in the seventh grade. The total score average for PedsQL was 81.58 ± 13.65, and the mean total score for SDQ was 25.02 ± 4.813. A positive and significant correlation was found between "behavioral problems" subscale score of the SDQ and all subscales of PedsQL except the "physical health" subscale as well as the positive and significant correlation between the mean total scores of PedsQL and SDQ. It was observed that the quality of life of the students is affected negatively as the difficulties experienced during adolescence increase. Some recommendations were made to reveal the problems experienced by school-age adolescents and to increase their quality of life.